Pengaruh Media Assemblr EDU Berbasis Augmented Reality terhadap Kemampuan Berpikir Tingkat Tinggi Siswa pada Materi Sistem Ekskresi - Putri Lubis, Febrianti; Manalu, Kartika; Widya Ulfa, Syarifah (JURNAL BIOSHELL, 2025)
The reason of this think about was to decide the impact of Increased Reality-based Assemblr Edu media on students' high-level considering aptitudes within the excretory framework fabric at MAN 2 Mandailing Natal. This consider may be a sort of quantitative investigate with a quasi-experimental plan chosen by cluster irregular choice for the pretest, posttest, and control gather plan. The populace of this consider was four classes of review XI IPA understudies of Madrasah Aliyah Negeri 2 Mandailing Natal, with course XI IPA-I as the exploratory lesson and XI IPA-2 as the control lesson. The investigate instrument was within the frame of ten exposition questions. The autonomous test T test appeared that Ha was acknowledged and H0 was rejected based on the theory test, which delivered a sig esteem (2-tailed) of 0.000 < 0.05 and 0.01. This shows that teaching materials based on Augmented Reality Assemblr Edu have an influence on advanced cognitive abilities